Professional Training of Border Guards in Ukraine: Challenges and Opportunities Related to Emerging Security Threats - Nataliya V. Bhinder (Educational Process: International Journal)
Professional training of border guards is closely connected with Ukraine’s national development, its stability and economic prosperity. Due to emerging security threats, the training of future border guards in Ukraine has recently undergone radical changes including the reconsideration of professional competence. According to its reviewed profile, professional competence of border guards means integral unity of knowledge, skills, personal qualities, and values that help them perform their professional duties. Professional competence of border guards is the desired result of their training. The content of professional training for border guards is therefore an important aspect. Changes in the tasks facing the border agency has caused significant rethinking of training content for border guards, resulting in new subjects, sections, modules and topics. As information has to be transferred effectively to trainees, a range of teaching techniques was innovated in order to achieve the pedagogical intention. The innovative techniques include simulation technologies, horizontal learning, innovative lectures, training courses, information and communication technologies, interactive technologies, as well as game-based and project-based learning. These techniques are proven to be more effective in comparison to traditional methods. Despite some unresolved issues, the system of professional training for border guards in Ukraine has shown outstanding results. Further development and improvement will lead to the formation of professional competence of border guards at the desired high level.